PELAKSANAAN PERJANJIAN SEWA MENYEWA PERALATAN BERKEMAH ANTARA PIHAK PENYEWA DENGAN TEMPAT PENYEWAAN ALAT DI ARVIN ADVENTURE PEKANBARU - Windu Nursalisa; Firdaus Firdaus; Meriza Elpha Darnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
A rental agreement to rent camping equipment between the lessee and the lessee is aform of legal relationship to meet the needs or interests of a matter. In this case the partieshave their respective rights and obligations. However, in reality this still causes problemscaused by one of the parties, both the tenants and Arvin Adventure. This clearly needs to beinvestigated because if one of the parties commits a default, then everything must be inaccordance with the applicable laws and regulations. If this is not implemented, it is possiblethat injustice will occur to the aggrieved party.The formulation of the problem posed is how is the implementation of the campingequipment rental agreement between the lessee and the equipment rental place ArvinAdventure Pekanbaru and how is the settlement of the camping equipment tenant in the eventof a default on the equipment rented by Arvin Adventure Pekanbaru. This research is asociological legal research, a research carried out by going directly to the location of theresearch object in order to obtain the required data.The results of this study indicate that the implementation of the camping equipmentrental agreement between the lessee and the equipment tenant at Arvin Adventure Pekanbaruis in accordance with the provisions of Article 1313 of the Civil Code and Article 1548 of theCivil Code. However, in reality this still causes problems which result in losses experiencedby Arvin Adventure Pekanbaru, namely defaults committed by the lessee and problemsarising because of the lessor. Settlement of these problems was resolved based onnegotiations between the two parties. In the case of a camping equipment rental agreement,each party must know which rights and obligations it has and the parties must have goodfaith in entering into the agreement.Keywords: Performance, Lease Agreement, Camping Equipment